2014
DOI: 10.1371/journal.pone.0110378
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Interleukin-8 and CD163-Positive Cell-Infiltration in Tumor Tissues in Patients with Oral Squamous Cell Carcinoma

Abstract: PurposeWe investigated whether serum interleukin (IL)-8 reflects the tumor microenvironment and has prognostic value in patients with oral squamous cell carcinoma (OSCC).Experimental DesignFifty OSCC patients who received radical resection of their tumor(s) were enrolled. Preoperative sera were measured for IL-8 by ELISA. Expression of IL-8 and the infiltration of immune cells in tumor tissues were analyzed by an immunohistochemical staining of surgical specimens.ResultsWe found that disease-free survival (DFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 24 publications
3
34
0
2
Order By: Relevance
“…For IL‐8, Fujita et al demonstrated that disease‐free survival was significantly longer in the Stage I/II OSCC patients with low serum IL‐8 levels compared to those with high levels. The tumor expression of IL‐8 and the density of CD163‐positive cells in the tumor invasive front were associated with the serum IL‐8 level, and an increase was correlated with worse clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For IL‐8, Fujita et al demonstrated that disease‐free survival was significantly longer in the Stage I/II OSCC patients with low serum IL‐8 levels compared to those with high levels. The tumor expression of IL‐8 and the density of CD163‐positive cells in the tumor invasive front were associated with the serum IL‐8 level, and an increase was correlated with worse clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 8 (CXCL8 gene, IL8 protein) is a member of the pro-inflammatory CXC chemokine gene family. Expression levels are elevated in the saliva of oral cancer patients, and high serum IL8 levels correlate with a poor clinical outcome in OSCC (41,42). The interleukin encoded by the IL1A gene is a potent mediator of inflammation and is involved in epidermal barrier function (43).…”
Section: Par-2 Activationmentioning
confidence: 99%
“…IL‐8 is a cytokine involved in tumor growth and angiogenesis in a variety of malignancies . In fact, IL‐8 is differentially regulated, but often found to be increased in OSCC tumors . Decreased IL‐8 observed in these cells following Gas6 treatment could be attributed to poorly characterized functions of IL‐8 in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…29 In fact, IL-8 is differentially regulated, but often found to be increased in OSCC tumors. 30 Decreased IL-8 observed in these cells following Gas6 treatment could be attributed to poorly characterized functions of IL-8 in tumor development. Perhaps a specific role for IL-8 during tumor formation exists, but it is not necessarily required for invasion or metastasis of already transitioned OSCC cells.…”
Section: Gas6 In Oscc Cell Invasion and May Explain The Presence Of Hmentioning
confidence: 99%